Strategy Asean Membangun Sense of Community - Anik Yuniarti (Jurnal Paradigma, 2012)
ASEAN has been making effort to realize the ASEAN Community with the enhancing of the common identity and sense of community of the ASEAN. In that process, the people of ASEAN is the central objective of the ASEAN Community. The “ASEAN people Oriented” encourage participation of the ASEAN people to the process of ASEAN integration in three pillars, namely the ASEAB Political and Security Community, ASEAN Economic Community and ASEAN Socio-Cultural Community. To realise the goal of a people-centred ASEAN Community, The ASEAN Socio-Cultural Community aims to contribute to realizing an ASEAN Community that is people-oriented and socially responsible with a view to achieving enduring solidarity and unity among the peoples and Member States of ASEAN. This research describes the ASEAN efforts to develop “we feeling” and “sense of community” in ASEAN.